PERANCANGAN INTERIOR TIME CAPSULE THRIFT SHOP CENTER DI KOTA DENPASAR - Erick Calvin Samudji; Ni Kadek Yuni Utami; Putu Surya Triana Dewi (Jurnal PATRA, 2019)
With the rise of “sustainable life” activities or lifestyles in the modern era, nowadays people become sensitive and understand about this lifestyle, many things have been developed and started to be done such as minimalist patterns and lifestyles, such as lifestyle to have the goods that are needed and not desired. People start competing to clean their goods by making a full selection of all items in the house and removing items that are not needed, this method is known as “Tidying up” or the art of tidying things. However, this raises various other problems, like the accumulation of household waste that occurs because of the method. Seeing the magnitude of the impact produced by the method, to overcome this problem a thrift shop center is needed in Denpasar and research is carried out using methods that are able to solve the problem, like research that uses structured parameters, like qualitative analysis methods carried out through the process of data analysis from various literatures and interviews with related parties, resulting in a design that accommodates the community to sell or to donate used items to the place of sale of used goods that maintain the value of the goods and places that educate the public that used goods or used clothing basically have high value too.